Reconfigurable Dual Band Antenna using Varactor Diode - Ali Mohammed Ahmedalsayaghi; Thennarasan Sabapathy; Mohamed Nasrun Osman; Shanmuka Rooban Gunasekaran; Sri Man Kumari Gollu; Divya Gayathri Poripireddy (Geviva Publisher, 2025)
This paper presents a dual-band frequency reconfigurable microstrip antenna integrated with an Electromagnetic Band Gap (EBG) structure for modern wireless communication applications. The proposed antenna operates at two key frequency bands of 1.8 GHz and 2.4 GHz and is fabricated on a Rogers 4003C substrate to achieve low dielectric loss and stable radiation performance. Frequency reconfigurability is achieved by embedding varactor diodes across strategically etched slots on the radiating patch, allowing continuous tuning through DC bias voltage control without altering the physical structure of the antenna. The EBG structure is employed to suppress surface wave propagation and enhance antenna gain and radiation stability. Simulation and experimental results demonstrate effective frequency tuning from 1.68–1.88 GHz and 2.38–2.81 GHz with stable impedance matching and directional radiation patterns. The proposed antenna is suitable for compact and reconfigurable wireless systems such as IoT and 5G applications.